Pertumbuhan dan Kandungan Klorofil Anggur Laut (Caulerpa Sp) Menggunakan Teknik Budidaya Berbeda - Valentine, Riris Yuli; Tangguda, Sartika; Hariyadi, Dimas Rizky; Sudiarsa, I Nyoman (Journal Galung Tropika, 2021)
Sea grapes have high economic potential. The development of sea grape cultivation is inseparable from its cultivation techniques. The research objective was to determine the daily growth rate and chlorophyll content of sea grapes in different cultivation techniques. The research was conducted from September to November 2020 at the Polytechnic of Marine and Fisheries, Kupang, East Nusa Tenggara. The treatment in this study was a different cultivation technique with 3 treatments, namely by spreading it (scattering technique), using the substrate (substrate technique), and combining the spread and substrate (combined technique). The results showed no difference in daily growth rate and chlorophyll content even though using different cultivation techniques. The intensity of sunlight more influences the daily growth rate and chlorophyll content. Water quality parameters during the study supported the daily growth rate.